Socio - economic consequences of Ebola virus outbreaks in West Africa - Mashi, AminaLawal; Yusof, Rohana @ Norliza (2014)
The recent Ebola virus outbreaks in some West African countries which according to world health organisation has so far affected many countries has raise scholarly attention on preventive measures to combat the disease.The objective of this paper therefore is to review existing literature on Ebola virus: Its historical development, its classification, it’s made of transmission and treatment as well as access its socio-economic consequences on affected victims, communities and nations.The method of data collected is secondary using textbooks, journals, newspapers, health bulletins/magazines, annual reports of various national and international organizations etc.The findings revealed that at least 3000 people, out of which over 2000 have died within 2 to 3 weeks, which constitutes serious health treats to humans and wildlife as well as the socioeconomic well-being of the affected nations. The paper recommends (amongst others) a holistic approach in tackling the menace of Ebola virus as one of the most deadly disease known to human society in recent history.